2011
DOI: 10.1590/s0104-42302011000100022
|View full text |Cite
|
Sign up to set email alerts
|

Tromboprofilaxia: recomendações médicas e programas hospitalares

Abstract: MDCT allowed diagnosis of different types of endoluminal thrombosis in patients submitted to endovascular repair of aortic abdominal aneurysm. Utilization of this minimally invasive diagnostic technique should be encouraged in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 65 publications
(103 reference statements)
0
7
0
21
Order By: Relevance
“…A ACCP indica aos pacientes clínicos, estratificados com alto risco, a tromboprofilaxia anticoagulante farmacológica, e como medidas não farmacológicas preconizam-se: meias de compressão graduadas, intermitentes e dispositivos pneumáticos de compressão (3) . Nesta pesquisa, 26 (53,06%) pacientes de alto risco utilizaram a profilaxia medicamentosa, em consonância com outros estudos (6,20) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A ACCP indica aos pacientes clínicos, estratificados com alto risco, a tromboprofilaxia anticoagulante farmacológica, e como medidas não farmacológicas preconizam-se: meias de compressão graduadas, intermitentes e dispositivos pneumáticos de compressão (3) . Nesta pesquisa, 26 (53,06%) pacientes de alto risco utilizaram a profilaxia medicamentosa, em consonância com outros estudos (6,20) .…”
Section: Discussionunclassified
“…Para quase um quarto dos pacientes com TEP, a apresentação clínica inicial é morte súbita (5) . No Brasil, um registro incluindo mais de 27.000 pacientes cirúrgicos e clínicos, evidenciou a subutilização de profilaxia para TEV em 25% dos pacientes em alto risco e em 45% daqueles com risco moderado, predominando em pacientes não cirúrgicos (6) .…”
Section: Introductionunclassified
“…As such, VTE is considered the greatest cause of avoidable death in hospital settings. 1,[3][4][5] It is a common disease among hospitalized patients, and can emerge as a complication of other clinical or surgical conditions, but it can also occur spontaneously in apparently healthy people. 6 According to the American College of Chest Physicians' (ACCP) 8th consensus on VTE prevention, almost all hospitalized patients have at least one risk factor for VTE, and around 40% have three or more.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important not to omit such measures in patients for who they are indicated. [4][5][6][7][8][9] However, it has been observed that thromboprophylaxis prescription rates are low and, when thromboprophylaxis is administered, it tends to be incorrect, despite the fact that protocols are available to guide health professionals. 6,[10][11][12] This study was conducted to evaluate the VTE risk profiles of recently-admitted clinical and surgical patients and to assess the thromboprophylactic measures administered during the first 24 hours after admission.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] However, few studies have been conducted with the objective of formulating strategies and providing guidance in the form of hospital-wide thromboprophylaxis programs. 11,12 Machado 13 recommends that a multidisciplinary team should be assembled made up of people who understand the importance of pharmacological prophylaxis, in order to improve the frequency and quality of provision of VTE prophylaxis. 14,15 In turn, a study published by Rocha et al 11 proposed that a commission should be created in all hospitals with a mission to encourage VTE prophylaxis using educational lectures.…”
Section: Introductionmentioning
confidence: 99%